The Effect of National Student Financial Aid Scheme on Student’s Access to Tertiary Education in a Selected University in The Western Cape - Xolela Sokhweba; Lawrence Obokoh; Babatunde Abiola; Chidinma Caroline Oji (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
The changes in South Africa implies that institutions of higher learning have become substantially a space for various individuals who historically would have found it difficult to access them. In striving to make tertiary education more accessible, the state and intuitions of higher learning perceived that incorporation is not just the evacuation of racial exclusion. It also requires support for students who basically cannot take up their studies because of financial constraints. South Africa is currently experiencing astronomical increase in the demand for tertiary education, with most of the potential students unable to afford the cost of tertiary education in the country. In order to solve the fees challenge, the government inaugurated the National Student Financial Aid Scheme (NSFAS) to provide financial assistance to students from middle- or low-income households in South Africa. After more than twenty-one years of operations, the effects of the scheme to student access to finance is scarcely available in the literature. This research makes use of mixed-method to examine the effects of NSFAS on student access to finance. The data collected from 501 students and 5 NSFAS administrative staff were analysed using the partial least square structural equation model and Nvivo for the qualitative data. The result reveals a positive effect of NSFAS on students’ access to finance for tertiary education. The results further reveal that despite the positive effect of the scheme, there exist some challenges that impinge on students’ smooth access to the funds which need to be addressed by the policy makers.